Analisis Pemahaman Konsep Dasar Biologi Peserta didik MA Plus Nurul Islam Sekarbela Pada Materi Jaringan - Evina Apriani; Nugrahaini Widyastari; Dedi Riyan Rizaldi; Nilwan (Lembaga Einstein College (LEC), 2025)
This study aims to analyze the level of understanding of basic Biology concepts among grade XI MIPA students at MA Plus Nurul Islam Sekarbela, particularly on the topic of Plant and Animal Tissues. The background of this research arises from the low level of students’ conceptual understanding in Biology, which often leads them to rely on memorization rather than meaningful comprehension. This research employed a descriptive qualitative method with a case study approach. Data were collected through a test consisting of 15 multiple-choice questions and 5 essay questions, then analyzed through data reduction, data presentation, and conclusion drawing. The results showed that the highest student score was 52.0, the lowest was 16.0, and the average was 31.2, indicating that students’ understanding of tissue concepts remains low. Factors contributing to this low understanding include limited learning resources that rely solely on textbooks, lack of reading and reviewing activities, the teacher’s teaching methods, and individual differences in students’ abilities to grasp concepts. This study is expected to serve as a reference for Biology teachers in designing more effective learning strategies to enhance students’ conceptual understanding.